Hubungan Antara Teks dan Konteks dalam Iklan di Televisi - Maria, Maria Cladina Nadeak; Rahayu, Sri (UIR PRESS, 2022)
This research is motivated by the author's interest in advertising language. Where advertising is one of the communication tools used to attract consumen or invite the audience to buy a product. This is what interests the author to analyze the relationship between text and context in advertisements. The sentences contained in advertisements on television are used as a source of research, because in advertisements on television there are texts and contexts that are used to make it easier for audience to understand the intent or purpose of the advertisements they watch. This is intended so as not to be wrong in buying or consuming a product. The problem of this research is how is the relationship between text and context contained in advertisements on television. This study aims to determine the relationship of text and context in advertising on television. The data collected by the researcher will be described, analyzed, and concluded in detail so that it can be see how the relationship between text and context in television advertisements is. Researchers divides advertisements into three categories, namely advertisements for food products, beverage products and beauty products. The theory used in this study is the theory of the relationship between text and context proposed by Wijana and Rohmadi (2009). The method used is descriptive qualitative research method. The data sources of this study were obtained from advertisements that aired on television stations, namely: SCTV, RCTI, Trans 7, ANTV, TRANS TV, INDOSIAR, and GTV. The technique used is by listening to the advertisements that appear on television, then browsing on YouTube on the internet network to make it clearer in terms of sound, being able to repeat when observing the advertisement images, and making it easier to analyze the data. The results of the study indicate that there is an appropriate relationship between text (speech) and context (state/situation) in advertisements for food, beverage and beauty products. Where the text (speech) spoken is in accordance with the situation described. In addition to the relationship, this study also succeeded in finding food and beverage product advertisements where the text and context were not related. This is because the text (speech) is not in accordance with the context (state/situation) described. Finally, the research shows that there is an advertisement in which the text (speech) and context (state/situation) have no relationship. This is indicated by the text (speech) that is not in accordance with the context (state/situation) described.